Involvement of H1 and H2 receptors and soluble guanylate cyclase in histamine-induced relaxation of rat mesenteric collecting lymphatics - Kurtz, Kristine H. (2014)
OBJECTIVE: This study investigated the roles of the H1 and H2 histamine receptors, nitric oxide (NO) synthase, and soluble guanylate (sGC) cyclase in histamine-induced modulation of rat mesenteric collecting lymphatic pumping. METHODS: Isolated rat mesenteric collecting lymphatics were treated with 1–100 μM histamine. Histamine receptors were blocked with either the H1 antagonist mepyramine or the H2 antagonist cimetidine. The role of NO/sGC signaling was tested using the arginine analog L-NAME, the sGC inhibitor ODQ, and sodium nitroprusside (SNP) as a positive control. RESULTS: Histamine applied at 100 μM decreased tone and contraction frequency (CF) of isolated rat mesenteric collecting lymphatics. Pharmacologic blockade of either H1 or H2 histamine receptors significantly inhibited the response to histamine. Pretreatment with ODQ, but not L-NAME, completely inhibited the histamine-induced decrease in tone. ODQ pretreatment also significantly inhibited SNP-induced lymphatic relaxation. CONCLUSIONS: H1 and H2 histamine receptors are both involved in histamine-induced relaxation of rat mesenteric collecting lymphatics. NO synthesis does not appear to contribute to the histamine-induced response. However, sGC is critical for the histamine-induced decrease in tone and contributes to the drop in CF.